N−H Bond Formation at a Diiron Bridging Nitride. Issue 35 (9th June 2020) - Zhang, Shaoguang; Cui, Peng; Liu, Tianchang; Wang, Qiuran; Longo, Thomas J.; Thierer, Laura M.; Manor, Brian C.; Gau, Michael R.; Carroll, Patrick J.; Papaefthymiou, Georgia C.; Tomson, Neil C.
Abstract: Despite their connection to ammonia synthesis, little is known about the ability of iron‐bound, bridging nitrides to form N−H bonds. Herein we report a linear diiron bridging nitride complex supported by a redox‐active macrocycle. The unique ability of the ligand scaffold to adapt to the geometric preference of the bridging species was found to facilitate the formation of N−H bonds via proton‐coupled electron transfer to generate a μ ‐amide product. The structurally analogous μ ‐silyl‐ and μ ‐borylamide complexes were shown to form from the net insertion of the nitride into the E−H bonds (E=B, Si). Protonation of the parent bridging amide produced ammonia in high yield, and treatment of the nitride with PhSH was found to liberate NH3 in high yield through a reaction that engages the redox‐activity of the ligand during PCET. Abstract : A diiron bridging nitride complex supported by a geometrically flexible, redox‐active macrocycle was synthesized and characterized by X‐ray crystallography and Mössbauer spectroscopy. Treatment of the electrophilic nitride with PhSH afforded NH3 in high yield through a reaction that engages the redox‐activity of the ligand during proton‐coupled electron transfer followed by protonolysis.